Medication Adherence and Quality of Life in Patients With Depression at Psychiatric Hospital in Surakarta, Indonesia - Yulianti, Tri; Adha, Dinda Caesaria (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Non-adherence to depression treatment may result in elevated risk of disease development, morbidity, and premature mortality, along with a deterioration in quality of life. This study is to investigate the correlation between medication adherence and quality of life among patients with depression receiving treatment in a psychiatric hospital in Surakarta, Indonesia. This cross-sectional quantitative study on depression was undertaken at the Psychiatric Hospital in Surakarta from March to June 2025. The instruments employed were the MARS-10 and WHOQoL-BREF questionnaires, both of which were translated into Indonesian. Spearman’s rho was used to assess the correlation between medication adherence and quality-of-life ratings. SPSS 29 was used to analyse, with a p-value < 0.05 deemed significant. Of the 110 patients who participated, the majority were aged 18-35 years (51.8%), female (51.8%), had 12 years of education or more (62.7%), and were unmarried (57.3%). A majority were employed (59.1%), received treatment for 6-12 months (46.4%), and exhibited no comorbidities (90.9%). The mean treatment adherence score among patients was 8.15 ± 2.02. Sixty-three patients (57.3%) demonstrated good adherence to their medication. The correlation test results between treatment adherence and the quality of life in patients with depression indicated a statistically significant relationship (p < 0.001; r = 0.550). Increased adherence to medication correlates positively with improved quality of life in patients suffering from depression.